Amulya Reddy : citizen scientist - Reddy, Amulya K. N.; Rajan, S. Ravi. (New Delhi : Orient BlackSwan, 2009)
Articles by Amulya Reddy on appropriate technology and energy; includes a brief autobiography; with reference to India.
"Amulya Reddy : a select bibliography" (p. [344]-364).
Includes bibliographical references and index.
Keywords: REDDY, AMULYA K. N; ENERGY POLICY; APPROPRIATE TECHNOLOGY; RURAL ELECTRIFICATION